Islamic Education in the Digital and Post-Truth Era: Building Mediating Narratives - Supriyatno, Triyo; Yasin, Ahmad Fatah; Susilawati, Samsul; Koesoemawati, Titien (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The digital revolution and post-truth phenomena have dramatically changed the landscape of Islamic education. Truth is no longer determined by epistemic authority but by algorithmic visibility and emotional resonance. This paper explores how Islamic education can construct mediating narratives that bridge tradition and modernity in the digital era. Using a qualitative-descriptive method based on literature review and conceptual analysis, the study investigates the epistemological, pedagogical, and ethical challenges facing Islamic educators. The findings reveal that Islamic education must reconstruct its learning models through three strategies: (1) epistemic mediation — integrating traditional sanad values with digital literacy; (2) pedagogical mediation — developing dialogical learning models that promote critical and spiritual intelligence; and (3) narrative mediation — constructing inclusive digital narratives rooted in hikmah and akhlaq (Islamic Moral). These findings highlight the importance of digital ethics, critical thinking, and spiritual literacy as the foundation of Islamic education in the post-truth era.